Factors Affecting Economic Growth and Poverty Rate in Kutai Timur District - Wiryadi Tamrin; Rusdiah Iskandar; Aji Sofyan Effendi (International Journal of Science and Society, 2022)
East Kutai Regency has the second largest area in East Kutai Regency. In various ways, the local government has tried to increase economic growth and poverty alleviation, but these problems have not achieved the desired results. This study aims to determine the direct and indirect effects of private investment, labor force, infrastructure spending, human development index on economic growth and poverty levels in East Kutai Regency. To analyze the data used path analysis. The data used is secondary data in the form of time series data for 2007-2021. The results of this study indicate that the direct influence of Private Investment, Labor Force, Human Development Index on growth has a positive direction but is not significant. In contrast, infrastructure spending on economic growth has a positive approach. Then the direct effect of private investment, the human development index on poverty, is positive and not significant if it has the direction. The direct effect of the Labor Force, Infrastructure Expenditure on the Poverty Level is negative and significant. The poverty rate through economic growth has a positive and significant direction. The indirect effect of the Labor Force on the Poverty Level through economic growth has a negative and insignificant direction. The indirect effect of infrastructure spending on poverty levels through economic growth has a negative and significant direction.